Valoración y cumplimiento de las normas existentes con relación a la contaminación atmosférica en la ciudad de Neiva (2021)
One of the great problems that man has generated, in his process of evolution, is associated with environmental pollution as a result of the accelerated consumption of everything type of goods and services products that in their entirety generate high-impact waste and whose decomposition times can take up to thousands of years, which bring about consequences on the quality of life of the population. Air pollution is one of these problems that affects to a greater or lesser extent proportion to all large cities, and refers to the presence in the atmosphere of substances that cause serious inconvenience, risk or damage to human beings and property of any kind. nature, that is, animals, plants and artificial material objects; its damage level is associated with the quality and quantity of the substances that are emitted into the atmosphere by, mainly, human sources classified as fixed or mobile; hence the Law of environment contains different instruments aimed at controlling the quality and quantity of these substances in the air, such as standards for air emission and immission levels.